Myrmica rubra microhabitat selection and putative ecological impact. (21st November 2018) - Warren, Robert J.; Mathew, Abby; Reed, Katelyn; Bayba, Sonya; Krupp, Kevin; Spiering, David J.
Abstract : 1. Myrmica rubra (European fire ant) has invaded northern latitude coastal areas in North America. This macroscale distribution suggests that M. rubra is moisture‐ and temperature‐limited, but the distribution of the invaded range may reflect the legacy of original introduction locations preserved by limited dispersal. 2. This study examined a two‐decade population change in M. rubra (1994–2015) and the microscale abiotic (moisture and temperature), biotic (plants), anthropogenic (pesticide) and physiological (thermal tolerance) limits on the invasion at the Tifft Nature Preserve in Buffalo, NY (U.S.A.). Changes in the abundance of native ants and other invertebrates were also examined. 3. Despite localised declines with pesticide treatments, overall M. rubra forager abundance increased 27% between 1994 and 2015. Abundance increased the most in the warmest areas (native ants were unaffected by temperature), but M. rubra colony locations were strongly linked to higher soil moisture and lower soil temperature. Myrmica rubra ants also exhibited relatively low thermal tolerances consistent with high‐latitude and high‐elevation ants. 4. Where local M. rubra populations increased the most, native ant species decreased, and where local M. rubra populations declined, native ant species increased. Some arthropod species had lower abundance with M. rubra presence, but the impacts were less striking. 5. Myrmica rubra population growth was promoted at the microhabitat scale where relatively higher temperatures prompted foraging, and relatively lower temperatures and high moisture supported nesting. These results suggest that macroscale M. rubra invaded‐range distributions in northern climates near coastal areas are replicated at the microscale where the ant prefers cooler, moister microsites. Abstract : North American invasions by the European fire ant ( Myrmica rubra ) are limited to coastal areas at higher latitudes, suggesting abiotic limitations or legacies of their original introductions. Myrmica rubra behaviour (foraging and nest location) and the ant's physiological thermal tolerances suggest the ant is physically limited to relatively cooler and wetter microhabitats. The ability to maintain exceedingly dense populations for, at a minimum, 35 years appears to impose considerable ecosystem impacts through food acquisition, while corresponding to dramatic drops in the native ant community.